2020
DOI: 10.1002/adom.202001845
|View full text |Cite
|
Sign up to set email alerts
|

Narrowband Emission from Organic Fluorescent Emitters with Dominant Low‐Frequency Vibronic Coupling

Abstract: Organic fluorescent emitters with narrowband emissions are highly desirable for high‐resolution organic light‐emitting diode (OLED) display technology. In principle, this can be achieved by specifically controlling the intrinsic structural relaxation and vibronic coupling in the excited state. Here, a design strategy to realize narrowband emission of organic fluorescent emitters is proposed by significantly enhancing the low‐frequency vibronic coupling strength (Λ) while simultaneously reducing the high‐freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
120
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(122 citation statements)
references
References 45 publications
2
120
0
Order By: Relevance
“…in the emission spectrum owing to the involvement of vibrational progression separated by the vibrational frequency. 30 Based on the above analysis, it can be concluded that lowering the reorganization energies of the excitation and emission processes can be achieved by restricting the structural deformation between the ground and excited states, which may impart small Stokes shift and narrowband emission to TADF molecules eventually. S11 and Table S1), which are well consistent with the theoretically calculated results (Table S2).…”
Section: Figure 2 Calculated Homo and Lumo Distributions Energy Band Gaps Oscillator Strengths And Molecular Surface Electrostatic Potentmentioning
confidence: 92%
See 1 more Smart Citation
“…in the emission spectrum owing to the involvement of vibrational progression separated by the vibrational frequency. 30 Based on the above analysis, it can be concluded that lowering the reorganization energies of the excitation and emission processes can be achieved by restricting the structural deformation between the ground and excited states, which may impart small Stokes shift and narrowband emission to TADF molecules eventually. S11 and Table S1), which are well consistent with the theoretically calculated results (Table S2).…”
Section: Figure 2 Calculated Homo and Lumo Distributions Energy Band Gaps Oscillator Strengths And Molecular Surface Electrostatic Potentmentioning
confidence: 92%
“…Generally, the enhanced low-frequency and suppressed high-frequency vibronic coupling are conducive to narrow FWHM. [30][31][32] For DtCzB-DPTRZ, the representative normal vibration modes with large contribution to reorganization energies are nearly distributed in all-frequency regions. However, the observed reorganization energies for the different normal vibration modes of DtCzB-DPTRZ have extremely small values (< 20 cm −1 ).…”
Section: Figure 2 Calculated Homo and Lumo Distributions Energy Band Gaps Oscillator Strengths And Molecular Surface Electrostatic Potentmentioning
confidence: 98%
“…In this regard, the deplanarized/ sterically hindered MR-TADF skeleton should be designed with caution to reduce vibrational progression and retain high color purity. [17] Herein, we demonstrate a novel strategy to realize MR-TADF motif with concurrent ultrahigh color purity, efficiency, and concentration-resistance by shielding the B/N based chromophore with carbazolyl units. The target emitter BN-CP1 is derived by covalent linking the blueish-green BN-Cz skeleton with 1,3-di(9H-carbazol-9-yl)benzene (mCP), and an isomeric emitter BN-CP2 with flattened geometry is also constructed for comparison (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…18 Large structural changes between the ground and excited states are responsible for the broad emission. 41 We exclude excimer or aggregate emission as the origin of the broad emission as the emission remains broad in dilute solution. We also note that the orthogonal arrangement of the phenyl substituent on the boron centre should effectively inhibit excimer or aggregate formation (see Fig.…”
Section: Photophysical Propertiesmentioning
confidence: 99%